Comparative analysis of the proximate and elemental composition of the blue crab Callinectes sapidus, the warty crab Eriphia verrucosa, and the edible crab Cancer pagurus. Issue 2 (February 2016) - Zotti, Maurizio; Coco, Laura Del; Pascali, Sandra Angelica De; Migoni, Danilo; Vizzini, Salvatrice; Mancinelli, Giorgio; Fanizzi, Francesco Paolo
Abstract: The proximate composition and element contents of claw muscle tissue of Atlantic blue crabs ( Callinectes sapidus ) were compared with the native warty crab ( Eriphia verrucosa ) and the commercially edible crab ( Cancer pagurus ). The scope of the analysis was to profile the chemical characteristics and nutritive value of the three crab species. Elemental fingerprints showed significant inter-specific differences, whereas non-significant variations in the moisture and ash contents were observed. In the blue crab, protein content was significantly lower than in the other two species, while its carbon content resulted lower than that characterizing only the warty crab. Among micro-elements, Ba, Cr, Cu, Li, Mn, Ni, and Pb showed extremely low concentrations and negligible among-species differences. Significant inter-specific differences were observed for Na, Sr, V, Ba, Cd and Zn; in particular, cadmium and zinc were characterized in the blue crab by concentrations significantly lower than in the other two species. The analysis of the available literature on the three species indicated a general lack of comparable information on their elemental composition. The need to implement extended elemental fingerprinting techniques for shellfish quality assessment is discussed, in view of other complementary profiling methods such as NMR-based metabolomics.